Analysis of Hydroquinone Content in Whitening Cream by Spectrophotometry UV-Vis Method - Efprio Nensa Kurniawan; Fajar Nugraha; Hadi Kurniawan (Journal Syifa Sciences and Clinical Research, 2022)
Hydroquinone is an ingredient that is often added in whitening creams with the aim of whitening the skin. According to BPOM Regulation No.23 of 2019, hydroquinone has been banned from its use as a bleach or lightener in cosmetics. The use of hydroquinone can only be used for nails with a level of 0.02%, as well as hair dye oxidizers with a maximum level of 0.3%. The mechanism of hydroquinone in whitening the skin is the toxic effect of hydroquinone on melanocytes, and through inhibition of the process of melanin formation. This study aims to identify and determine the levels of hydroquinone contained in whitening creams circulating in Pontianak City. The research method used in this study is descriptive non-experimental, where as many as 10 samples of whitening cream circulating in Pontianak City were obtained using purposive sampling techniques. Identification of hydroquinone is carried out qualitatively using FeCl3 1% reagent, and benedict reagent. Determination of hydroquinone levels in the sample is done quantitatively using a UV-Vis spectrophotometer. Based on the calculation of validation parameters, the equation y = 0.0251x – 0.0029, linearity value with relation coefficient (r) of 0.9999, %recovery of 100.15%, precision with a value of %RSD of 0.4899%, LOD of 0.2742 ppm and LOQ of 0.9140 ppm. Based on the results obtained, as many as 8 samples of positive whitening creams contained hydroquinone with a sample level of A of 3.1630%; sample B of 2.7322%; C sample of 2.5335%; sample D of 2.3216%; G sample is 2.5118%; H sample of 3.3171%; sample I was 2.4409 and sample J was 0.5571%.